Recent Advances in Engineered Stem Cell-Derived Cell Sheets for Tissue Regeneration - Kim, Hyunbum (Polymers (Basel), 2019)
The substantial progress made in the field of stem cell-based therapy has shown its significant potential applications for the regeneration of defective tissues and organs. Although previous studies have yielded promising results, several limitations remain and should be overcome for translating stem cell-based therapies to clinics. As a possible solution to current bottlenecks, cell sheet engineering (CSE) is an efficient scaffold-free method for harvesting intact cell sheets without the use of proteolytic enzymes, and may be able to accelerate the adoption of stem cell-based treatments for damaged tissues and organs regeneration. CSE uses a temperature-responsive polymer-immobilized surface to form unique, scaffold-free cell sheets composed of one or more cell layers maintained with important intercellular junctions, cell-secreted extracellular matrices, and other important cell surface proteins, which can be achieved by changing the surrounding temperature. These three-dimensional cell sheet-based tissues can be designed for use in clinical applications to target-specific tissue regeneration. This review will highlight the principles, progress, and clinical relevance of current approaches in the cell sheet-based technology, focusing on stem cell-based therapies for bone, periodontal, skin, and vascularized muscles.